1997
DOI: 10.1046/j.1423-0410.1997.7220085.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Prevention of Transfusion‐Associated Human Immunodeficiency Virus Transmission in Sub‐Saharan Africa

Abstract: International aid to establish and maintain HIV antibody screening programmes, implementation of sound criteria for transfusion, and the search for HIV risk factors to use as donor exclusion criteria must be expanded in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 59 publications
(143 reference statements)
0
19
1
Order By: Relevance
“…[2]. Contrary to reports from across sub‐Saharan Africa which have previously indicated a substantial burden of HIV infections attributed to blood transfusion [2,17,19–23], this study identified no evidence of laboratory or reporting error and only a theoretical risk of HIV transmission because of acute infections potentially detectable by NAT. These results demonstrate that a profound reduction in the risk of transfusion‐associated HIV infection is possible in resource‐limited countries with severe, generalized HIV epidemics, and validate the NBTS decision to implement the WHO recommendations for national blood services.…”
Section: Discussioncontrasting
confidence: 76%
“…[2]. Contrary to reports from across sub‐Saharan Africa which have previously indicated a substantial burden of HIV infections attributed to blood transfusion [2,17,19–23], this study identified no evidence of laboratory or reporting error and only a theoretical risk of HIV transmission because of acute infections potentially detectable by NAT. These results demonstrate that a profound reduction in the risk of transfusion‐associated HIV infection is possible in resource‐limited countries with severe, generalized HIV epidemics, and validate the NBTS decision to implement the WHO recommendations for national blood services.…”
Section: Discussioncontrasting
confidence: 76%
“…New donors aged 16 to 20 years donating at a school venue are generally deemed to be safe and their blood is collected in blood bags with anticoagulant. The new donors in age group 21 to 44 years are in the high‐risk category and their blood is collected in blood packs without an anticoagulant as part of risk management for HIV and other transfusion‐transmissible infections (TTIs) . As an additional safety measure for window period–phased donations there are instances when a dry pack is used on repeat donors.…”
Section: Methodsmentioning
confidence: 99%
“…The new donors in age group 21 to 44 years are in the high-risk category 14, 18 and their blood is collected in blood packs without an anticoagulant as part of risk management for HIV and other transfusion-transmissible infections (TTIs). [19][20][21][22] As an additional safety measure for window period-phased donations there are instances when a dry pack is used on repeat donors. This applies to all lapsed repeat donors and repeat donors aged 21 to 30 years coming for their second donations.…”
Section: Donor Risk Classificationmentioning
confidence: 99%
“…The impact of other less expensive strategies on HIV transmission risk reduction, such as donor deferral and the non-use of donations from higher risk sub-populations has been highlighted in low income countries 273-277 . Unfortunately, these cost-effective strategies are not being applied consistently 273,274,278-280 . While progress towards improving safe and adequate supplies of blood is being made 278 , continued government commitment is critical for ensuring quality, safety, and adequacy of the blood supply, particularly in lower income nations where challenges in capacity, logistics, and infrastructure are common.…”
Section: Transfusionmentioning
confidence: 99%